Emotional Availability in Samples of Mothers at High Risk for Depression and With Substance Use Disorder - Frigerio, Alessandra; Porreca, Alessio; Simonelli, Alessandra; Nazzari, Sarah (Frontiers in Psychology, 2019)
Background. Maternal Substance Use Disorder (SUD) and depression have been extensively associated with dysfunctions in parent-child interactions. However, few studies have compared caregiving behaviors of these mothers. The current study aims to explore maternal emotional availability (EA) in mothers with maternal SUD and depressive symptoms in order to investigate whether these conditions represent a different risk gradient for early parenting. Methods: Mother-infant relationship was investigated in 18 mothers with substance abuse disorder (SUD), 11 mothers at risk for depression and 39 mothers from general population. The dyads were videotaped during a free-play session and the quality of parent-child interactions was assessed using the EA Scales (EAS) and the Emotional Attachment and EA Clinical Screener (EA2-CS). Results: Mothers with SUD scored lower on sensitivity, non-intrusiveness, and non-hostility with respect to the low-risk sample, whereas mothers at risk for depression scored lower on sensitivity and non-hostility compared to the latter. No significant differences between mothers with SUD and mothers at risk for depression emerged on the EAS, whereas different specific classifications on the EA Clinical Screener were found for the SUD (i.e. Complicated), depression (i.e. Detached) and low-risk (i.e. Emotionally Available) samples. Conclusions: If the current findings are replicated, they might have significant implications for selecting targets of early mother-infant interventions.